2019
DOI: 10.15252/emmm.201810124
|View full text |Cite
|
Sign up to set email alerts
|

Liver ASK1 protects from non‐alcoholic fatty liver disease and fibrosis

Abstract: Non‐alcoholic fatty liver disease (NAFLD) is strongly associated with obesity and may progress to non‐alcoholic steatohepatitis (NASH) and liver fibrosis. The deficit of pharmacological therapies for the latter mainly results from an incomplete understanding of involved pathological mechanisms. Herein, we identify apoptosis signal‐regulating kinase 1 (ASK1) as a suppressor of NASH and fibrosis formation. High‐fat diet‐fed and aged chow‐fed liver‐specific ASK1‐knockout mice develop a higher degree of hepatic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 72 publications
(111 reference statements)
1
59
0
Order By: Relevance
“…As liver-sequestered Ly6G-positive neutrophils preferentially express CEACAM1-L isoform at 6 hours after reperfusion, while neutrophils express robust cytoplasmic CC1 after reperfusion (unpublished observations), the putative role of CEACAM1-L in neutrophil regulation in IRI-OLT awaits future studies. ASK1, a redox-sensitive upstream activator of the JNK and p38 arms of the MAPK pathway (23), may be activated by ROS, TNF-α, ER stress, UV irradiation, or calcium overload, placing ASK1 as a signaling node in which different stressors converge (24)(25)(26)(27). An increasing number of studies focus on the role of ASK1 in the pathophysiology of NASH (27), whereas the efficacy and tolerability of an ASK1 inhibitor, selonsertib, has been reported in a phase 2, randomized, open label clinical trial in patients with NASH (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As liver-sequestered Ly6G-positive neutrophils preferentially express CEACAM1-L isoform at 6 hours after reperfusion, while neutrophils express robust cytoplasmic CC1 after reperfusion (unpublished observations), the putative role of CEACAM1-L in neutrophil regulation in IRI-OLT awaits future studies. ASK1, a redox-sensitive upstream activator of the JNK and p38 arms of the MAPK pathway (23), may be activated by ROS, TNF-α, ER stress, UV irradiation, or calcium overload, placing ASK1 as a signaling node in which different stressors converge (24)(25)(26)(27). An increasing number of studies focus on the role of ASK1 in the pathophysiology of NASH (27), whereas the efficacy and tolerability of an ASK1 inhibitor, selonsertib, has been reported in a phase 2, randomized, open label clinical trial in patients with NASH (28).…”
Section: Discussionmentioning
confidence: 99%
“…ASK1, a redox-sensitive upstream activator of the JNK and p38 arms of the MAPK pathway (23), may be activated by ROS, TNF-α, ER stress, UV irradiation, or calcium overload, placing ASK1 as a signaling node in which different stressors converge (24)(25)(26)(27). An increasing number of studies focus on the role of ASK1 in the pathophysiology of NASH (27), whereas the efficacy and tolerability of an ASK1 inhibitor, selonsertib, has been reported in a phase 2, randomized, open label clinical trial in patients with NASH (28). A recent in vitro study has also demonstrated the contribution of ASK1/p-p38 signaling axis in cell type-specific death under cold stress (11).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently culture medium was replaced every other day until the day of experiment. Differentiated subcutaneous cells were transfected with 100 nM of siRNA SMARTpools, siRNA targeting ASK1 or non-targeting siRNA SMARTpools, control siRNA for 24 h, as previously described for HepG2 cells 55 . LPS treatment was started 24 after ASK1 siRNA transfection.…”
Section: Rna Extraction and Quantitative Reverse Transcription-pcr (Rmentioning
confidence: 99%
“…Subsequent experiments using tissue-specific knockout models revealed that neither adipocytes nor myeloid cells are responsible for the phenotype (S3L-Q Figs). A recently published study revealed that the hepatocyte-specific knockout of ASK1 in HFD-fed mice leads to a higher degree of hepatic steatosis, inflammation, and fibrosis, along with slightly impaired glucose clearance [65]. Therefore, hepatic fibrosis induced by ASK1 depletion in hepatocytes may at least partially explain the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hepatic fibrosis induced by ASK1 depletion in hepatocytes may at least partially explain the mechanism. Nonetheless, we observed a significant increase in fasting glucose levels in global ASK1KO mice (S3E and H Figs), but fasting glucose levels did not seem to be altered in hepatocyte-specific ASK1KO mice [65], suggesting that there are other ASK1-dependent regulatory mechanisms for glucose homeostasis. One possibility is a malfunction in insulin secretion, but this is unlikely given the previous results using the hyperglycemic clamp method [58]; however, impaired insulin secretion in fasted HFD-fed ASK1KO mice is possible.…”
Section: Discussionmentioning
confidence: 99%